Association of millennial parenting styles, dietary and the incidence of stunting - Silpia, Nana; Palimbo, Adriana; Lestari, Yayuk Puji; Salmarini, Desilestia Dwi (Health Sciences International Journal, 2025)
Background: Stunng, a chronic nutrional issue among toddlers, connues to be a global and naonal public health concern. It reflects the cumulave effects of inadequate nutrion and poor parenng pracces. Millennial parenng styles and dietary habits play a pivotal role in influencing stunng outcomes, parcularly in regions like Banjarmasin, Indonesia. Objective: This study aims to analyze the correlaon between millennial parenng styles, dietary paerns, and stunng incidence among toddlers in the Pekauman Health Center area. Methods: A cross-seconal study was conducted in May 2024 involving 127 toddlers aged 2–5 years and their parents. Data were collected using height measurements and validated quesonnaires on parenng styles and dietary pracces. Chi-square tests were employed to analyze relaonships, with a significance level of α = 0.05. Results: The study revealed that 64.6% of toddlers were stunted. Among parents, 61.4% exhibited a "less" effecve parenng style, and 61.4% provided diets that did not meet nutrional recommendaons. Significant associaons were found between parenng styles,dietary paerns, and stunng incidence (p < 0.001). Poor parenng pracces and inadequate diets were idenfied as crical factors contribung to stunng. Conclusion: Millennial parenng styles and dietary pracces significantly influence stunng incidence. Intervenons to improve parental knowledge and dietary pracces are essenal for addressing stunng in toddlers. Future research should explore innovave strategies, including digital plaorms, to enhance parental engagement and nutrion educaon